Face Transplant: Status of Current Supporting Technology to Plan and Perform the Operation and Monitor the Graft in the Postoperative Period. Issue 4 (June 2018) - Caterson, Edward J.; McCarty, Justin C.
Abstract : Abstract: Face transplant has rapidly advanced since the first operation in 2005, and to date, 40 partial or full-face transplants have been performed. The safety and efficacy of this operation are aided at all phases by supporting technologies. These include advanced imaging techniques to plan the operation, devices to monitor the flap in the immediate perioperative period, and noninvasive imaging and serum markers to monitor for acute and chronic rejection. Some of the technologies, such as those used in the immediate perioperative period, have extensive evidence supporting their use, whereas those to detect acute or chronic rejection remain investigational. The technologies of today will continue to evolve and make the operation safer with improved outcomes; however, the most significant barrier for face transplant continues to be immunologic rejection.